Role of Bioinformatics in Crop Improvement (Global Journal of Science Frontier Research, 2017)
Bioinformatics plays a significant role in the development of the agricultural sector, agro-based industries, agricultural by-products utilization and better management of the environment. With the increase of sequencing projects, bioinformatics continues to make considerable progress in biology by providing scientists with access to the genomic information. It is believed that we will take on another giant leap in bioinformatics field in next decade, where computational models of systems wide properties could serve as the basis for experimentation and discovery. Agricultural bioinform -atics areas that need focus would be are data curation and need for the use of restricted vocabularies. Being an interface between modern biology and informatics it involves discovery, development and implementation of computational algorithms and software tools that facilitate an understanding of the biological processes with the goal to serve primarily agriculture and healthcare sectors with several spinoffs.
Keywords: agricultural bioinformatics; crop improve ment; bioinformatics; biology; information-technology